Magnetically inflatable SPS with energy storage capability - Ehsani, M.; Bilgiç, Mehmet Oruç; Patton, A. D.; Mitra, J. (IEEE, 1995)
A new approach to superconductive magnetic energy storage (SMES) for solar power satellite (SPS) with inherent rigidity is introduced in this paper. The rigidity of this SMES originating from the electromagnetic forces within it, can eliminate the need for mechanical building blocks for support structure. This force can also be used for the deployment of the system in space. In addition, the storage capability of the system allows its use in low Earth orbit (LEO) which reduces the launching and transmission costs. The paper also discusses the basic design and the operation of the proposed SPS system.
Keywords: Energy storage; Low earth orbit satellites; Samarium; Superconducting magnetic energy storage; Solar energy; Power transmission; Satellite ground stations; Photovoltaic systems; Solar power generation; Superconductivity